Elevated CO2 Enhances Dynamic Photosynthesis in Rice and Wheat - Kang, Huixing; Zhu, Ting; Zhang, Yan; Ke, Xinran; Sun, Wenjuan; Hu, Zhenghua; Zhu, Xinguang; Shen, Haihua; Huang, Yao; Tang, Yanhong (Frontiers in Plant Science, 2021)
Crops developed under elevated CO2 (eCO2) exhibit enhanced leaf photosynthesis under steady states. However, little is known about the effect of eCO2 on dynamic photosynthesis and the relative contribution of the short-term (substrate) and long-term (acclimation) effect of eCO2. We grew an Oryza sativa japonica cultivar and a Triticum aestivum cultivar under 400 μmol CO2 mol−1 air (ambient, A) and 600 μmol CO2 mol−1 air (elevated, E). Regardless of growth [CO2], photosynthetic responses to a sudden increase and then a decrease in light intensity were characterized under 400 (a) or 600 μmol CO2 mol−1 air (e). By using the Aa, Ae, Ea and Ee treatments, we expected to quantify the acclimation effect (Ae vs. Ee and Aa vs. Ea) and substrate effect (Aa vs. Ae and Ea vs. Ee). In comparison with Aa treatment, both steady-state photosynthetic rate (PN) and induction state (IS) were higher under Ae and Ee treatment but lower under Ea treatment in both species. However, IS reached at the 60 sec after the increase in light intensity, the time required for photosynthetic induction, and induction efficiency under Ae and Ee treatment did not differ significantly from those under Aa treatment. The substrate effect increased accumulative carbon gain (ACG) during photosynthetic induction by 45.5% in rice and by 39.3% in wheat, whereas the acclimation effect decreased ACG by 18.3% in rice but increased it by 7.5% by wheat. Thus, elevated CO2, either during the growth or at the measurement, enhances dynamic photosynthetic carbon gain in both the crop species. This indicates that photosynthetic carbon loss due to induction limitation may be reduced under future high CO2 world.